2021
DOI: 10.3389/fphar.2021.689032
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Microbubble–Facilitated Inner Ear Delivery of Gold Nanoparticles Involves Transient Disruption of the Tight Junction Barrier in the Round Window Membrane

Abstract: The application of ultrasound microbubbles (USMBs) enhances the permeability of the round window membrane (RWM) and improves drug delivery to the inner ear. In this study, we investigated the efficiency of USMB-aided delivery of chitosan-coated gold nanoparticles (CS-AuNPs) and the mechanism of USMB-mediated enhancement of RMW permeability. We exposed mouse inner ears to USMBs at an intensity of 2 W/cm2 and then filled the tympanic bulla with CS-AuNPs or fluorescein isothiocyanate-decorated CS-AuNPs (FITC-CS-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, the possible variations of these parameters make it hard to truly study their toxicity. Initial in vivo studies researching their utility as an inner ear contrast agent observed no effect on the morphology of the hair cells [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the possible variations of these parameters make it hard to truly study their toxicity. Initial in vivo studies researching their utility as an inner ear contrast agent observed no effect on the morphology of the hair cells [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of FDA approvals for the use of NPs to treat various auditory diseases has increased [ 11 ]. In a preclinical setting, locally applied chitosan-coated gold nanoparticles (Cs-AuNPs) in the rats’ tympanic bulla did not compromise the animals’ hearing thresholds [ 12 ]. However, AuNPs have not yet been utilized in treating inner ear diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies are under investigation to enhance drug entry into the inner ear through the RWM using magnetic fields ( Du et al, 2013 ; Shapiro et al, 2014 ), ultrasound ( Lin et al, 2021 ), RWM microperforations ( Aksit et al, 2021 ), or nanocarriers ( Jaudoin et al, 2021 ). Approaches to overcome or at least decrease intracochlear basal-apical concentration gradients involve the application of RWM low-frequency micro vibrations ( Flaherty et al, 2021 ) or direct intracochlear drug application ( Chen et al, 2005 ; Hahn et al, 2012 ; Ayoob and Borenstein, 2015 ; Plontke et al, 2017 ; Prenzler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors explored the efficiency of permeability induction by ultrasound and MBs and aided delivery of nanoparticles in a combined setting. By applying MBinduced sonoporation, the authors achieved transient reversible disruption of the epithelial tight junctions of the round window outer surface membrane, successfully improving site specific drug delivery [79]. Table 2 summarizes clinical trials using ultrasound-mediated therapeutic applications.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%